Spirituality - An Antidote to Corruption (Research Nepal Journal of Development Studies, 2022)
An antidote is a cure for sickness. Corruption is danger sickness of this 21st century and the antidote to the corruption sickness is no other than spirituality. This viewpoint paper engages with the spiritual insights against corruption at the individual level that might be a fundamental dimension for good governance. It explores Vedas and some of the mystic’s views on corruption. It urges that anti-corruption laws and offices alone will not be able to cope with corruption because power doesn’t corrupt, people are corrupt. Corruption is inside peoples’ hearts and minds. Hence, along with the various dimensions of good governance, academia needs to motivate the development of spiritual insight in people. It will develop a playful attitude in individual life with peace in mind and compassion in heart, instead of competition, hatred, and rat race behind success, money, position, status, and power.